2020
DOI: 10.1371/journal.pone.0230268
|View full text |Cite
|
Sign up to set email alerts
|

Spinal radiographic progression in axial spondyloarthritis and the impact of classification as nonradiographic versus radiographic disease: Data from the Swiss Clinical Quality Management cohort

Abstract: Objective To investigate whether spinal radiographic progression relates to structural damage at the sacroiliac level in axial spondyloarthritis (axSpA). Methods Patients classified as nonradiographic (nr-) and radiographic (r-) axSpA in the Swiss Clinical Quality Management cohort with radiographs performed every 2 years, scored according to the modified Stoke Ankylosing Spondylitis Spine Score (mSASSS), were included. The relationship between classification status and spinal progression during 2 years was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 46 publications
1
19
0
2
Order By: Relevance
“…[8][9][10] Subsequent works indicated, however, that such a retardation might be possible, especially if treatment is applied long-term, which is in line with our results, although there are some differences in terms of the study design, patient characteristics and definition of TNFi exposure in the intervals. [11][12][13][14][15][16][17][18] Indeed, it seems that the effect of anti-inflammatory treatment with TNFi cannot be observed immediately after treatment initiation-at least not with radiographs as the method of structural damage assessment. This is related to the fact that inflammation in the vertebral body is followed by the process of repair characterised by the replacement of the inflammatory-affected bone marrow by fibrous repair tissue that gives raise to new bone formation (syndesmophytes) later on.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10] Subsequent works indicated, however, that such a retardation might be possible, especially if treatment is applied long-term, which is in line with our results, although there are some differences in terms of the study design, patient characteristics and definition of TNFi exposure in the intervals. [11][12][13][14][15][16][17][18] Indeed, it seems that the effect of anti-inflammatory treatment with TNFi cannot be observed immediately after treatment initiation-at least not with radiographs as the method of structural damage assessment. This is related to the fact that inflammation in the vertebral body is followed by the process of repair characterised by the replacement of the inflammatory-affected bone marrow by fibrous repair tissue that gives raise to new bone formation (syndesmophytes) later on.…”
Section: Discussionmentioning
confidence: 99%
“…evident that a long-term suppression of inflammation might be necessary to see the effect of anti-inflammatory treatment on structural damage development. [11][12][13][14][15][16][17][18] The minimal duration of TNFi treatment that is needed to observe reduction of radiographic progression and the question if such an effect can also be observed in patients at an earlier disease stage remained uncertain.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Other correlation structures (‘independence’, ‘unstructured’ and ‘autoregressive’) were investigated in sensitivity analyses, and the resulting coefficients and CIs varied only slightly. The choice of covariates (baseline radiographic damage, sex, ASDAS, treatment with TNFi before the radiographic interval, treatment with NSAIDs at the start of the radiographic interval, current smoking and the duration of the radiographic interval) was informed by our previous investigations of spinal radiographic progression in SCQM 33 36. ASDAS, treatment with NSAIDs and current smoking were missing in 17%, 19% and 14% of the observations, respectively, and imputed using multiple missing value imputation by chained equations (MICE), assuming a missing-at-random data pattern.…”
Section: Methodsmentioning
confidence: 99%
“…Conventional radiology was found to be a useful tool for the evaluation of Achilles tendon enthesitis, according to a study conducted by Kim et al; in particular, they found bone erosions, retrocalcaneal recess obliteration and swollen posterior soft tissue were strongly associated with current painful posterior heels (27). In a Swiss cohort of patients with both nr-axSpA and r-axSpA, a 2-year study of radiographic progression showed structural damage, measured by mSASSS, was significantly lower in the first group (28). Interestingly, syndesmophytes development seemed to be usually preceded by sacroiliitis onset.…”
Section: Conventional Radiologymentioning
confidence: 97%